In vivo anticoccidial activity and immune response of Moringa oleifera and Vernonia amygdalina leaves against Eimeria magna and Eimeria media in rabbits - Konmy, Basile; Olounladé, Pascal Abiodoun; Adjobimey, Tomabu; Dansou, Christian Cocou; Adoho, Akouavi Carine Chimène; Tchetan, Esaïe; Alowanou, Georcelin Goué; Azando, Erick Virgile Bertrand; Adjanohoun, Adolphe; Doko Allou, Sanni-yo; Baba-Moussa, Lamine (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction The aims of this study were to determine the immune response and the anticoccidial activity induced by Moringa oleifera and Vernonia amygdalina leaves in rabbits infected with Eimeria magna and Eimeria media. Methods Thirty-five-day-old rabbits, free from coccidia, were infested with 2.103 oocysts of Eimeria magna and Eimeria media, then received the acetone extract of the leaves of Moringa oleifera and Vernonia amygdalina at different doses by oral gavage. Results and discussion The inhibition of the excretion of oocysts was evaluated by the McMaster technique and the levels of cytokines (IL-4 and IL-12) and immunoglobulin IgG were assayed by the ELISA method. The in vivo efficacy on E. magna and E. media oocysts was 95.43% and 96.53% for Moringa oleifera and Vernonia amygdalina at 1000 mg/kg bw against 98% for the positive control. Interestingly the plant extracts increased the production of interleukin (IL) and immunoglobulins (Ig) compared to controls. Plasma IL-4 levels (pg/ml) in rabbits were 128.94 and 131.38; those of IL-12 (pg/ml) were 395.55 and 426.56, and then for those of IgG (μg/ml) were 14.70 and 13.94 respectively with the acetone extracts of Moringa oleifera and Vernonia amygdalina on D14 PT at 1000 mg/kg bw. This study indicates that Moringa oleifera and Vernonia amygdalina can be used as an alternative to synthetic anticoccidials. These plants could be used to increase the resistance of the immune system of rabbits to infestations of Eimeria species in rabbit farms.